ANÁLISIS DE CALIDAD DEL SERVICIO QUE PRESTA LA AGENCIA DE VIAJES ALFAMAR TRAVEL CIA. LTDA. DE LA CIUDAD DE LOJA. - Román Paladines, Tatiana Anabel (2020)
The project named “Analysis of the quality of service provided by the Alfamar Travel Travel Agency”, will allow the Travel Agency administrator to perform an analysis of the services offered as a company when offering quality services that meet the needs and desire of the clients. The quality of services, refers to the services offered to a certain user, which means providing value to the customer, that is to offer optimal conditions of use of the products or services, superior to those that the client expects to receive and at an accessible price. When we approach the concept of quality, it does not only refer to a good, it also refers to a service, only that the quality in this case is intangible. Due to the interest shown by companies to meet the quality and needs of customers in terms of the service provided, there was a need to define the term "quality in service." In order to carry out this research, a general objective was proposed “Analyze the quality of service provided by the travel agency “Alfamar Travel” Cia. Ltda. Of the city of Loja.” Which met the approach of three specific objectives applying various methods, as well as techniques, tools and instruments of investigation that allowed the fulfillment and development of the objectives obtaining significant results. For the development of the research, the inductive, deductive, analytical, synthetic and descriptive methods were used, which helped in the collection and selection of information, in order to establish results to later be analyzed and specify the possible solutions to improve the quality of services offered by the travel agency, together with the diagnostic matrix making an assessment of how the establishment is currently, the Servqual methodology was also used as a reference allowing customers to perceive the services, determined what the shortcomings are presented by the agency, also using techniques such as the interview, direct observation and survey that allowed the construction of the SWOT matrix resulting in the proposals to be made. For the achievement of the first Objective “Diagnose the current situation of the travel agency Alfamar Travel Cia. Ltda.”, Allowing to know how the travel agency is internally, through a situational diagnostic matrix based on the requirements for the travel agency of the MINTUR adapting it based on the needs of the company, therefore we proceeded to carry out the gathering of information to know if the travel agency meets the requirements that the matrix identifies such as: general data, permits of regulatory entities, regulations for the travel agency, minimum conditions, general requirements, infrastructure, services, as well as interviews with those involved in the company determined internal factors (strengths and weaknesses). For the second objective “Evaluate the quality of service offered by the travel agency Alfamar Travel Cia. Ltda.”, The Servqual Model was used but for the needs of the company it was modified structuring 5 items, taking as its main point the perception of clients on a Likert scale from 1 to 5, where 1 means very dissatisfied, 2 dissatisfied, 3 acceptable, 4 satisfied and 5 very satisfied according to each question that consists in analyzing the quality of the service in which it was done 115 people with a survey of 23 5 questions through the five dimensions: Tangible Elements, Empathy, Reliability, Responsiveness and Security, resulting in the tabulation of the shortcomings that customers perceive when receiving the service, subsequently proceeded to structuring the SWOT (opportunities and threats) according to each response I conclude with the strategy matrix, reflecting the external factors of the company to raising the possible strategies for improving it. The third objective is “Propose strategies for improving the quality of service of the Alfamar Travel Cía Travel Agency. Ltda.”, Once the SWOT was completed and the strategy matrix was constructed, the table with the characteristics, policies, values, indicators and goals to comply with its proposal designed with the purpose of contributing to the development and continuous advancement of the agency offering Quality services for customer satisfaction. In the results obtained, it can be seen in the first objective that it meets most of the requirements of Regulatory Entities, but nevertheless it still has a deficiency in some of the requirements for the proper functioning as a company. In the second specific objective it can be determined that the clients are not fully satisfied with the services received and the third objective was the proposal of the strategic objectives for a better quality of service. Finally, this research project shows the appropriate conclusions and recommendations pointed to the need to implement the proposed strategies to improve the quality of service and business management of the travel agency "Alfamar Travel", the strategies to be implemented is that the staff constantly train on issues related to customer service among others; It is also proposed to develop a manual of functions for the company; an evaluation system of the acquired service; expand the place to work with better efficiency and serve the customer; also to improve the agreements with tourist companies that will include all the requirements that a Hotel, restaurant and transport must meet; Finally, the acquisition of adventure sport equipment, with the results, attention, service and customer satisfaction are improved.